Single-cell imaging assay for rapid antimicrobial resistance testing - Kyropoulos, J (2021)
Antimicrobial resistance (AMR) is arguably one of the biggest healthcare challenges in the new century, the constant rise of which presents extra threat, projecting to cause 10 million deaths and billions of dollars in cost by 2050 if no action is taken. Drug-resistant pathogens have no border and can travel to any corner of the world, regardless of wealth or distance. One of the biggest challenges in addressing this rise of AMR is the low speed of current diagnostic methods, forcing physicians to prescribe inappropriate or unnecessary antibiotics before a diagnosis is reached, and such misuse inevitably exacerbates the rise of AMR. In this project, a proof-of-principle imaging assay was developed to significantly accelerate the procedure to reach a correct diagnosis. This assay used fluorescence in situ hybridisation (FISH) to detect RNA targets that led to the identification of bacterial speciation and the bacteria’s resistance to certain antibiotics. It was validated with laboratory and clinical isolates of E. coli with promising results. This project paved the way to a multiplex assay that would generate robust and reliable results within one hour.